APPLICATION OF GAMIFICATION TECHNIQUES TO CREATE A SUPPORTIVE LEARNING ENVIRONMENT IN HIGHER EDUCATION ENGLISH CLASSES - Assanova, A.B.; Kinzhibaeva, A.S. (Publisher of Kostanay Regional University named after Akhmet Baitursynuly, 2025)
The article presents a brief overview of the history of the issue, discusses the reasons for the growing popularity of gamification at the present stage, as well as considers the main principles and methods of its application, provides examples of educational games. The authors describe the key principles and practical approaches to the use of gamification in the process of teaching foreign languages in higher education institutions. This technology combines content, game elements and pedagogical techniques in order to increase student motivation. This approach allows us to consider gamification as an innovative pedagogical technology that can be effectively applied for different age groups, at different stages of the educational process and within different types of activities.
Keywords: gamification; game practices; information and communication technologies; foreign language; training programs